2020
DOI: 10.1007/s10815-020-01810-w
|View full text |Cite
|
Sign up to set email alerts
|

Motives and considerations regarding PGT in couples carrying a structural chromosomal abnormality: a qualitative exploration

Abstract: Purpose This study aims to describe the motives and considerations of couples carrying a structural chromosomal abnormality deciding on preimplantation genetic testing (PGT). Methods A qualitative exploratory study was conducted using semi-structured dyadic interviews with 13 couples (N = 26) carrying a structural chromosomal abnormality. All couples had an informative consultation in our PGT centre in the Netherlands. Results Almost all couples considered PGT or natural conception combined with prenatal diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The main motive to opt for PGT was the desire to have a healthy child which is in line with results of previous studies (Genoff Garzon et al 2018 ). A previous study on couples with a balanced chromosomal rearrangement showed that this group perceived PGT as the fastest way to establish an ongoing pregnancy (De Krom et al 2015 ; De Krom et al 2020 ). However, in our study, couples mainly opted for a natural conception without genetic testing to avoid a medical trajectory and they perceived this as the fastest way to establish a pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The main motive to opt for PGT was the desire to have a healthy child which is in line with results of previous studies (Genoff Garzon et al 2018 ). A previous study on couples with a balanced chromosomal rearrangement showed that this group perceived PGT as the fastest way to establish an ongoing pregnancy (De Krom et al 2015 ; De Krom et al 2020 ). However, in our study, couples mainly opted for a natural conception without genetic testing to avoid a medical trajectory and they perceived this as the fastest way to establish a pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis identifies if the pregnancy had normal or abnormal genetics and the sex of the pregnancy. This information can help identify the likelihood of a genetic abnormality in one or both parents that might be contributing to RM 5 8…”
Section: Introductionmentioning
confidence: 99%